CRAFT Method to Minimize Material Handling Cost in Automotive Component Industry - Aisyah, Siti; Ra, Taufiqurrahman; Sumasto, Fredy; Imansuri, Febriza; Aminudin, Muhammad; Rusmiati, Emi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
In automotive component manufacturing, an efficient plant layout minimizes material handling costs (MFCs). The problem is the high material handling costs for the production of 2DIN Radio Bracket MK 56660 at PT XYZ because it is produced at two factories, Factory 1 and Factory 9, which are pretty far apart. Using the Computerized Relative Facility Allocation Technique (CRAFT), this study aims to optimize the plant layout by exploring alternative configurations that facilitate cost-effective material handling. The initial assessment of the 2DIN Radio Bracket MK 56660 layout revealed a material transfer cost. Applying the CRAFT method, two different alternative proposals for layout improvement emerged. The first alternative showed a reduction in material transfer costs of IDR 476.11. In contrast, the second alternative resulted in a slightly higher cost of IDR 476.21. The study findings concluded that the first alternative, with the lowest cost of IDR 476.11, is the preferred choice to improve the plant layout and minimize MMF. This study provides practical insights into plant layout optimization in the automotive component industry and underscores the effectiveness of the CRAFT method in identifying cost-effective solutions to material handling challenges.